206k views
2 votes
Anyone can help me to solve this?​

Anyone can help me to solve this?​-example-1

2 Answers

2 votes

Answer:

1. 2x²-x-6=0

2. x²-7x+10=0

3. a²+13a+12=0

4. 2x²-x-6=0

5. 2x²-x-6=0

Explanation:

Expand the factors by multiplying each terms in the bracket to the others in the other bracket.

Then collect like terms and simplify.

Something like :

(x+2)(2x-3)=0

x*2x*x*-3*2*2x*2*-3=0

2x²-3x+4x-6=0

2x²-x-6=0

User Bakudan
by
5.5k points
0 votes

Answer:

1.)
\sf 2x^2 +x - 6=0

2.)
\sf x^2-7x+10=0

3.) 
\sf a^2 + 13a + 12 = 0

4.)
\sf 2x^2 +x - 6=0

5.)
\sf 2x^2 +x - 6=0

Explanation


\sf Formula: (a+b)(c+d) = ac + ad + bc + bd

2.)


\sf (x-2)(x-5)=0


\sf x^2-5x-2x+10=0


\sf x^2-7x+10=0

3.)


\sf (a+12)(a+1)=0


\sf a^2 + a + 12a + 12 = 0


\sf a^2 + 13a + 12 = 0

4.)


\sf (x + 2)(2x-3)=0


\sf 2x^2 -3x + 4x - 6=0


\sf 2x^2 +x - 6=0

5.)


\sf (x+2)(2x-3)=0


\sf 2x^2 -3x + 4x - 6=0


\sf 2x^2 +x - 6=0

Question 1, 4, 5 are same and repeated questions. Solution's same.

User Sohan Vanani
by
6.4k points